Strengthening Cybersecurity Awareness Through Education: The Expanding Role of Cyber Law in Academic Institutions - Nadry, Zabihullah; Hakimi, Musawer; Sirat, Abdul Wali; Popal, Zekrullah (Universitas Pendidikan Nasional, 2025)
As digital technologies continue to proliferate, university students are especially vulnerable to the risks associated with cyber threats, and there is a dearth of research related to the cybersecurity awareness of university students in a developing country context. The purpose of this study is to examine the cybersecurity knowledge, attitudes, and practices of first-year students at Kabul University in Afghanistan to determine the influence of gender, faculty, and awareness of cyber law on intentions to engage in secure online behavior. To collect data, we conducted a cross-sectional survey of 371 students who were recruited using stratified random sampling. Participants were introduced to and administered a survey using the Contextualized Cybersecurity Educational Research Instrument (CCERI), and data was analyzed on SPSS using descriptive statistics, independent samples t-tests, ANOVA, Chi-square tests, and multiple regression models. The results indicated that students had moderate to high levels of cybersecurity knowledge and generally positive attitudes, but that they demonstrated fewer secure practices and a knowledge-practice gap emerged. Male students and students from the Computer Science faculty had greater awareness of cybersecurity and higher recognition of phishing attempts than female students and students from the other faculties. Multiple regression models indicated that cybersecurity knowledge, attitudes, and awareness of the cyber law were significant predictors of secure behavior; this suggests that we need to develop and integrate educational interventions to support positive behaviors in terms of secure cyber practices. Our research adds new knowledge by integrating awareness of cyber law with cybersecurity behavior in Afghanistan as its own unique context. We conclude with recommendations for evidence-informed decisions to implement and develop institutionalized programs to address capacities in cybersecurity education for students in Afghanistan.